An option for optimising the radiographic technique for horizontal beam lateral (HBL) hip radiography when using digital X-ray equipment. Issue 2 (May 2016) - Charnley, C.; England, A.; Martin, A.; Taylor, S.; Benson, N.; Jones, L.
Abstract: Aim: To investigate the optimum technique for the horizontal beam lateral (HBL) hip projection considering image quality and radiation dose. Methods: Using digital radiography equipment an anthropomorphic phantom was positioned for a HBL projection of the hip. Radiographic exposures were undertaken across a range of acquisition parameters (tube potentials, source to image distances, object to detector distances, with and without an anti-scatter radiation grid/additional copper filtration). Each acquisition combination was imaged three times and the dose area product (DAP) and post-AEC mAs recorded. 168 images were acquired. A single observer evaluated five anatomical areas on all images using a two-alternative force choice technique. The reference image was selected based on the current locally accepted technique. 50 images out of the original 168 were independently assessed by a further four observers to ensure reliability of the results. Results: Image quality, when comparing all the images to the reference, was improved on in two cases; however the radiation dose had increased. 18 images had equal image quality with some having an 80% reduction in the DAP. In terms of the diagnostic acceptability, 51 were considered acceptable with a lower radiation dose. Conclusion: By optimising acquisition factors for the HBL hip projection the radiation dose to the patient can be reduced. Based on the findings the factors proposed for HBL hip projections are 90 kVp, 135 cm SID, 45 cm ODD, grid and 0.1 mm copper filtration. Highlights: We compare different horizontal beam lateral hip x-ray techniques. Image quality is assessed against radiation dose using an anthropomorphic phantom. We found the radiation dose can be reduced by 80% by altering the radiographic technique.